Globalization and Glocalization: Experiences in the Local Philippine Context - Ma. Divina Gracia Z. Roldan (Philippine Institute for Development Studies (PIDS), 2010)
The study examines local responses to globalization, with Cebu as a case in point. It describes the initiatives of the business, export, and ICT sectors in adjusting to global demands. Manifestations of glocalization are indicated in the increased role of local players, intensified global-local linkaging, and the translocal and decentralized nature of responses by government. Attendant issues and challenges concerning Cebu's glocal experience such as persistent poverty and increasing inequalities are also discussed.
Keywords: 330; globalization; Philippines; local governance; glocalization; Globalisierung; Kommunalverwaltung; Standortpolitik; Cebu; Philippinen